2011
DOI: 10.1521/ijgp.2011.61.4.556
|View full text |Cite
|
Sign up to set email alerts
|

Applying Motivational Interviewing Principles in a Modified Interpersonal Group for Comorbid Addiction

Abstract: The application of motivational interviewing (MI) principles in modified interpersonal group therapy (MIGT) addresses two gaps in the literature. First, it explicitly extends MIGT to non-abstinent, addicted patients who are in the precontemplative and contemplative stages of change in contrast to most MIGT models where abstinence is usually required. Second, it provides a novel, process-oriented group intervention for MI, in contrast to current applications of group-based MI which are more structured in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Several studies have shown that group treatment for dual disorder clients is an effective treatment component (Malat et al, 2011;Drake et al, 2007). In the analysis of components that clients appreciated, group meetings were named being helpful and valuable when there is a base of trust.…”
Section: Clusters and Themes Definitions And Examplesmentioning
confidence: 99%
“…Several studies have shown that group treatment for dual disorder clients is an effective treatment component (Malat et al, 2011;Drake et al, 2007). In the analysis of components that clients appreciated, group meetings were named being helpful and valuable when there is a base of trust.…”
Section: Clusters and Themes Definitions And Examplesmentioning
confidence: 99%